PRE-SERVICE ELEMENTARY TEACHERS’ WRITTEN COMMUNICATIONS: EXPLAINING MULTIPLICATION USING AREA REPRESENTATIONS - Saleh, Sitti Fithriani; Purwanto, Purwanto; Sudirman, Sudirman; Hidayanto, Erry (International Journal of Insights for Mathematics Teaching (IJOIMT), 2018)
This research was conducted to proposepre-service elementary teachers? (PsET)written communication in explaining multiplication representation, especially using area representation. Communication has an important role in learning process. Through communication, one can show or confirm his or her knowledge. The subjects of this research were 9 university students as the PsET. The subjects were asked to write the explanation of multiplication using area representation on a paper. After that, the researcher confirmed it by asking the subjects to re-explain that mentioned representation on a board as if they really taught elementary school students. From the result of this research, it is identified three main findings that can be obtained from written communication of the PsET, they are 1) expressing procedural and conceptual knowledge, 2) expressing ability in constructing connection, and 3) improvingthe confidence of PsET.